Diagnosis, monitoring, and treatment of primary ciliary dyskinesia: PCD foundation consensus recommendations based on state of the art review. Issue 2 (29th September 2015) - Shapiro, Adam J.; Zariwala, Maimoona A.; Ferkol, Thomas; Davis, Stephanie D.; Sagel, Scott D.; Dell, Sharon D.; Rosenfeld, Margaret; Olivier, Kenneth N.; Milla, Carlos; Daniel, Sam J.; Kimple, Adam J.; Manion, Michele; et al.
Summary: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous, rare lung disease resulting in chronic oto‐sino‐pulmonary disease in both children and adults. Many physicians incorrectly diagnose PCD or eliminate PCD from their differential diagnosis due to inexperience with diagnostic testing methods. Thus far, all therapies used for PCD are unproven through large clinical trials. This review article outlines consensus recommendations from PCD physicians in North America who have been engaged in a PCD centered research consortium for the last 10 years. These recommendations have been adopted by the governing board of the PCD Foundation to provide guidance for PCD clinical centers for diagnostic testing, monitoring, and appropriate short and long‐term therapeutics in PCD patients.Pediatr Pulmonol. 2016;51:115–132 . © 2015 The Authors. Pediatric Pulmonology Published by Wiley Periodicals, Inc.